Carcass characteristics of marketable size farmed catla, Catla catla (Hamilton, 1822). (22nd April 2013) - Sahu, B. B.; Raghunath, M. R.; Meher, P. K.; Das, P. C.; Mishra, B.; Senapati, D. K.; Sahu, A. K.; Jayasankar, P.
Summary The present study investigates carcass traits of farmed freshwater Catla catla for important information in calculating yield and/or providing data for programming machine/manual handling. For this purpose specimens of C. catla ranging from 1880 to 2150 g were collected from grow‐out culture ponds of the Central Institute of Freshwater Aquaculture, Odisha State, India. Carcass yield, offal yield and carcass cutability were assessed. The percentage of head yield was highest (31.2%) in comparison to other carp species. Gutted yield and final dressed yield of 2 kg market class catla amounted to 85.4 and 54.1%, respectively. The average meat : bone ratio in filleting was reported to be 3 : 9. The middle cut of catla had both the highest total yield percentage and highest meat yield. Dry matter, ether extract and protein percentage was highest in the fore cut followed by the middle and hind cuts.